Kill promise - Blade, Scott ([United States] Black Lion Media, 2022)
"Promises are meant to be kept. Especially a promise like this. Jack Widow is submarine-watching near Kitsap Naval Base, outside Seattle, when he runs into an old friend. In a hurry, his sailor buddy takes him to a prestigious medal ceremony: the Navy Cross. The event is a "big deal" because the medal is going to the first Native American woman recipient. Who is she? Lou Cosay is a highly decorated former sailor-turned-NCIS agent. She's smart, tough, and deadly. Admirals, Journalists, politicians, indigenous groups, and even the Secretary of the Navy are there. But when Cosay doesn't show up, it leaves everyone worried. What would make her miss such an important event in her life? Answering this question, Widow discovers she's vanished without a trace. Digging deeper takes him to Sawyer Lake, North Dakota, an off-grid kind of place. A place with deadly secrets. What's in Sawyer Lake? A promise. A promise that must be kept. A promise to kill. "
111349
Keywords: Missing persons -- Fiction; Murder -- Investigation -- Fiction; Thrillers (Fiction); Suspense fiction